Analisis dan Perancangan Tata Keloladan Pengelolaan Teknologi Informasi Berbasis Kerangka COBIT 5 DomainAlign-Plan-Organise (APO) (Studi Kasus:Diskominfo Jabar) - Felayati, Fiqha; Mulyana, Rahmat; Witjaksono, R. Wahjoe (Universitas Trilogi, 2018)
Based on the Regulation of the Minister of Communication and Information Technology number: 41/Per/Men/Kominfo/11/2007, to achieve good governance Diskominfo Jabar need to implement good governance and management of information technology (IT) practices in order to integrate organizational management to ensure that information technology is optimally utilized. But its implementation, IT governance of corporate has not been optimally applied. It is known from the results of enabler assessment done in this study. The focus of this research is the APO (Align, Plan, and Organize) domain COBIT 5 framework, so the assessment of the 7 enablers done is to know the current condition of IT governance in the APO process. The process of APO domains is also prioritized through 3 approaches: regulatory compliance, strategic alignment and risk approach based on COBIT 5 so it generates APO02 manage strategy, APO05 manage Portfolio, APO07 manage human resource, APO12 manage risk and APO13 manage security. The result of the assessment of the 7 enablers will show the gap with ideal conditions in COBIT 5 in order to implement good governance. Thus, this research will result in the recommendation of 7 enablers grouped into people, process and technology to address the previously identified gaps, in order to achieve the targeted conditions of IT governance Diskominfo Jabar on priority APO domains based on COBIT 5.